2020
DOI: 10.1155/2020/2826010
|View full text |Cite
|
Sign up to set email alerts
|

GDF15 Repression Contributes to 5-Fluorouracil Resistance in Human Colon Cancer by Regulating Epithelial-Mesenchymal Transition and Apoptosis

Abstract: Chemotherapy based on 5-fluorouracil (5-FU) is the standard approach for colon cancer treatment, and resistance to 5-FU is a significant obstacle in the clinical treatment of colon cancer. However, the mechanisms underlying 5-FU resistance in colon cancer cells remain largely unknown. This study aimed at determining whether 5-FU-resistant colon cancer cells undergo epithelial-mesenchymal transition (EMT) and apoptosis and the role of GDF15—a member of the transforming growth factor β/bone morphogenetic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…GDF15 neutralization in non-human primates decreased levels of cisplatin-induced weight [27][28][29]. Conversely, 5-FU-resistant CRC cells express lower levels of GDF15 compared to 5-FU-sensitive cells and transient expression of GDF15 restores sensitivity, suggesting that this gene plays an important role in 5-FU-mediated cell death [30]. Therefore, GDF15 likely plays a multiplex role in the response to chemotherapy and careful investigation is needed before combination therapies are considered.…”
Section: Pan-drug Gene Signature Contains Transcripts Critical To the Cellular Response To Chemotherapy In Crc Cells And Confirms Importamentioning
confidence: 99%
“…GDF15 neutralization in non-human primates decreased levels of cisplatin-induced weight [27][28][29]. Conversely, 5-FU-resistant CRC cells express lower levels of GDF15 compared to 5-FU-sensitive cells and transient expression of GDF15 restores sensitivity, suggesting that this gene plays an important role in 5-FU-mediated cell death [30]. Therefore, GDF15 likely plays a multiplex role in the response to chemotherapy and careful investigation is needed before combination therapies are considered.…”
Section: Pan-drug Gene Signature Contains Transcripts Critical To the Cellular Response To Chemotherapy In Crc Cells And Confirms Importamentioning
confidence: 99%
“…In addition, M SLN and GDF15 were found to be significantly upregulated (fold change = 12.24 for M SLN and fold change = 14.76 for GDF15 ) in colorectal cancer tissues, as well as to interact with colorectal-cancer-specific enhancers in colorectal cancer cells ( Figure 6 C, D). Mesothelin (MSLN) is reportedly associated with the prognosis of colorectal cancer [ 27 ], and growth differentiation factor 15 (GDF15) is reportedly associated with the recurrence and 5-fluorouracil resistance of colorectal cancer [ 28 , 29 , 30 ]. ChIP and HiChIP data showed that several colorectal-specific enhancers interact with M SLN and GDF15 , and some of these enhancers interact with M SLN or GDF15 through long-range chromatin interactions (>20 kb) ( Figure 6 C,D).…”
Section: Resultsmentioning
confidence: 99%
“…5-FU-resistant colon cancer cells have enhanced EMT and antiapoptotic capacity. Drug-resistant cells generally exhibit accelerated proliferation and distant metastases [59]. The combination of natural compounds with 5-FU treatment can inhibit colon cancer progression and metastases by inhibiting epithelial-stromal transformation and promoting apoptosis.…”
Section: -Fluorouracil (5-fu)mentioning
confidence: 99%